The Measurement of Health Inequalities: Does Status Matter? - Joan Costa-Font; Frank A. Cowell (Institute of Labor Economics (IZA), 2019)
Approaches to measuring health inequalities are often problematic in that they use methods that are inappropriate for categorical data. The approach here focuses on "pure" or univariate health inequality (rather than income-related or bivariate health inequality) and is based on a concept of individual status that allows a consistent treatment of such data. We use several versions of the status concept and apply methods for treating categorical data to examine self-assessed health inequality for the countries contained in the World Health Survey; we also use regression analysis on the apparent determinants of these health inequality estimates. Our findings indicate major differences in health-inequality rankings depending on the status concept. We find evidence that health inequalities vary with median health status alongside indicators of institutional performance.
Keywords: D63; H23; I18; 330; health inequality; categorical data; entropy measures; health surveys; upward status; downward status